“Harapan dan Tanggung-jawab Asimetris di Masa Pandemi Covid-19” - Charles Virgenius Setiawan (Sekolah Tinggi Widya Sasana, 2021)
Lévinas’ notion of responsibility has two characters: concrete and asymmetric. These two characters of responsibility can be capitalized to foster hope in the midst of the Covid-19 pandemic that is currently sweeping the world. An encounter with others, especially with those who are suffering from Covid-19, is not merely a physical encounter. This encounter gives birth to responsibility and realization that those who suffer are not “the others.” This awareness eliminates the desire to treat others as objects that can be used to fulfill their own needs. On the other hand, this awareness of responsibility breeds hope for those who suffer that they are not alone. In order to foster hope in those who suffer, the actions and responsibilities taken always have an asymmetric character.